Answer:
6.2+8.7+8.9x
Step-by-step explanation:
For expressions to be equivalent, they must simplify to the same lowest form. 8.9x+6.2+8.7 simplifies to 8.9x +14.9.
Each of the expressions below must simplify to 8.9x + 14.9 to be equivalent.
9x+6+9 = 9x + 15 NO
3.9+6.2+8.7x = 8.7x + 10.1 NO
3.7+8.9+6.2 = 18.8 NO
6.2+8.7+8.9 = 23.8 NO
6.2+8.7+8.9x = 8.9x + 14.9 YES
3.9+6.2x+8.7 = 6.2x + 12.6 NO
3.9x+8.7+6.2 = 3.9x + 14.9 NO
Answer:
There would be a straight line at -0.5 on the graph.
Step-by-step explanation:
Hope this helps
<h2><em>
:)</em></h2>
Answer:
<h3> FALSE</h3>
Step-by-step explanation:
The statement "The expression contains 2 terms." is false because the expression contains 3 terms: 7f, 15 and -2g
6 hamsters, 3 cats, and 1 bird = 38 legs.
6H + 3C + 1B = 30
H = 4 C = 4 B = 2
6*4 + 3*4 + 1*2 = 38
Hope this helped :)
Answer: 336 beads
Step-by-step explanation:
To find how many beads are in each layer, use the equation 12 x 7 = 84
Then multiply the amount of beads by each layer: 84 x 4 = 336